Polymorphism and promoter methylation-regulated mRNA expression of IFI6 gene affect meat quality in pigs - Watchara Laenoi; Muhammad Jasim Uddin; Asep Gunawan; Autchara Kayan (Italian Journal of Animal Science)
This study examined the association, promoter methylation of Interferon alpha-inducible protein 6 (IFI6) gene, and their effects on mRNA expression and meat quality traits in pig. Muscle samples (n=300) were randomly collected from the Longissimus thoracis et lumborum (LTL) to determine meat quality traits including drip loss, thawing loss, cooking loss, meat pH [at 45 minutes (pH45min) and at 24 hours (pH24h) post-mortem], shear force (for tenderness), and lightness (L*) in pigs. Genotyping was performed by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Muscle samples (5 per group) with divergent meat pH (low vs high) were selected for promoter methylation study using bisulfate and pyrosequencing. Muscle samples from animals (5 per group) with divergent phenotypes (low vs high meat pH and low vs high drip loss) were used for mRNA expression study by quantitative real-time polymerase chain reaction (qRT-PCR). Results showed that a polymorphism in IFI6 gene (g.370A>G) was significantly (P < 0.01) associated with meat pH24h. Furthermore, four CpG regions were identified in IFI6 promoter, of which DNA methylation in a CG site was higher in low meat pH24h group compared to high meat pH24h group (P < 0.05). The mRNA expression of IFI6 gene was significantly (P < 0.01) downregulated in low meat pH24h group than high meat pH24h group. This result postulated that high DNA methylation at CG site in the promoter region might downregulate the IFI6 gene expression, hence lower the muscle pH that might lead to higher drip loss and lower tenderness. Therefore, porcine IFI6 gene might be a potential candidate gene for meat quality trait in pig. Nevertheless, further research is needed to confirm the role of IFI6 gene in controlling meat quality traits in other commercial populations.